Tao-sheng's Commentary on the Saddharmapundarika-sutra: A Study and Translation - Kim, Young-ho (My University, 1985)
This dissertation provides a comprehensive study and complete translation of Tao-sheng's Commentary on the Saddharmapundarika-sutra (CSPS). This document occupies an important place in Chinese Buddhist literature. Its significance in the study of Chinese Buddhism can be described in two ways. Firstly, the CSPS was the first commentary ever written on the Lotus Sutra, which was to become a scripture of fundamental importance on the Far Eastern Buddhist scene, especially for the later Chinese Buddhist schools. Furthermore, it was the first commentary on any Buddhist scripture that was written in Chinese and structured in fully developed commentari al form. The CSPS set a pattern in many ways for later Buddhists to follow in terms of both structure and ideology. Secondly, the CSPS is a rich source of Tao-sheng's seminal ideas. Tao-sheng (ca. 360-434) has been regarded, both in his time and subsequently, as a uniquely creative and prophetic thinker. The CSPS, the only writing of Taosheng preserved in complete form, is essential to any study of Tao-sheng's own original thought. Most of his theses and arguments, which were controversial in his day, were originally propounded in his other writings, but the commentary may provide at least the general structure of Tao-sheng's thought. The thesis is composed of two main portions: "Study" (Part I-IV) and "Translation" (Part V). Part I sets out and clarifies the problems involved in the study of Tao-sheng, the aims and method of the present study. Part II as the introductory step to the main task involving the CSPS extensively examines Tao-sheng as a whole as reflected in other sources, in terms of his background, historical and biographical, his works, his doctrines, and his influence. Part III is devoted to a critical examination of the CSPS proper. Here I undertake an in-depth analysis in several different ways in respect with both form and content, or language and ideology. The analysis focuses on how Tao-sheng renders, successfully or otherwise, the ancient Indian system of religious thought into the current Chinese language, which was already laden with indigenous philosophical connotations. Here I also trace and reconstruct Tao-sheng's thought incorporated in the commentary in accordance with his distinct themes. Part IV reviews the findings and significance of the study conducted. In brief, the thesis is the first full-scale study of Tao-sheng and the commentary. Finally, a complete translation of the text is presented along with detailed annotations including the classical sources of Chinese philosophical terms used and numerous corruptions of the text. In light of the significance of Tao-sheng and the CSPS, the translation answers the need for a complete translation of the text into a modern language and will serve as a basis for further study.
Keywords: Saddharmapundarika; Translation